Response of the carnivorous Plicopurpura pansa (mollusca: gastropoda) and the herbivorous Chiton articulatus (mollusca: polyplacophora) to environmental factors in Acapulco, Mexico - García-Ibáñez, Sergio (Universidad Autónoma de Tamaulipas, 2014)
Gastropod Plicopurpura pansa and polyplacophoran Chiton articulatus are species that coexist in the rocky intertidal of the Mexican tropical Pacific. It has been reported that P. pansa is a predator of C. articulatus, and both are abundant and dominant species on the rocky coast of Acapulco, Guerrero, Mexico. This study analyzed the response patterns of relative density and lengths of both species to five specific environmental factors at four rocky shores of this region. During the periods October-December 2010, and February-April 2011, systematic samples of both species were collected. Study sites differed in the complexity of substratum and waves. The number of organisms per square meter and total lengths were recorded, as well as sea temperature, salinity and chlorophyll-α. Relative densities of each species varied in the study sites and in all cases they were greater than 1.0 org/m2. We observed a relationship between polyplacophoran length, and sea temperature, salinity and chlorophyll-α; a relationship between the length and abundance of the gastropod, and substratum complexity; and finally, we observed a greater abundance of polyplacophoran in the areas of high waves. Differentiated behaviors of both species were also observed, depending on the characteristics of the rocky shore and environmental factors. The abundance and length of the carnivorous P. pansa were closely related to the characteristics of the rocky shore surface. Over time, the length of herbivorous C. articulatus was associated with physical and chemical parameters of the sea; while spatially, abundances were related to substratum type and wave intensity.